Investigation of anticancer (breast cancer) activity of Moringa oleifera leaf extracts - Mirghani, Mohamed Elwathig Saeed; Ahmad Raus, Raha; Hossain, Nazia (Kulliyah of Engineering, International Islamic University Malaysia, 2016)
Moringa oleifera (M. oleifera) has been considered as food substance since ancient times and has also been used as a treatment for many diseases. Nowadays various therapeutic effects of M. oleifera such as antimicrobial, anticancer, anti-inflammatory, antidiabetic, and antioxidant effects have been successfully investigated. In this study M. oleifera methanol extraction was done on breast cancer cell (MCF-7) to obtain anti-cancer activity by incorporation with microtitrate tetrazolium (MTT) assay and it inhibited MCF-7 cell line with 87.13% in average at wavelength A570nm. Cell-lines were seeded at 2x105 cells per ml in a 100µl of media (DMEM 90% and serum 10%) per well in 96 well plates. Moreover, an optimization study was done in terms of temperature and incubation time by sonication. The optimum condition was found to be temperature 50⁰C and incubation time 45 min with medium frequency at sonication and it obtained 88.39% cancer cell growth inhibition by this condition. Additionally, this extract was also implemented on normal cell line (VERO) and the extract inhibited only 12.89%. Thus it showed greater cytotoxicity for cancer cells than for normal cells, strongly suggested that it could potentially be an ideal anticancer therapeutic candidate specific to cancer cells. These results suggested that extraction strategy adopted in this work could lead to several industrial applications and the potential therapeutic implications of the soluble extract from M. oleifera leaves extract in the treatment of various types of cancers